Philosophy of Life "Limuk Limor Kweunun Kweamam" in Maintaining Kinship Relationships in Lawawang Village (Masela Island District) - Tiwery, Rosefel (Indonesian Journal of Visual Culture, Design, and Cinema, 2025)
This study aims to examine the philosophy of life "Limuk Limor Kweunun Kweamam" as a guide to the kinship values ​​of the Lawawang Village community, Pulau Masela District. This philosophy represents the principles of togetherness, solidarity, and social responsibility in everyday life. This study uses a qualitative approach with ethnographic methods to explore in-depth understanding from traditional leaders, communities, and local cultural actors through in-depth interviews and participatory observations. The findings show that "Limuk Limor Kweunun Kweamam" is not just a symbolic expression, but rather a social framework that regulates relations between families, joint decision-making, and resolution of internal conflicts. This philosophy is passed down from generation to generation through customary practices and oral narratives, and is still relevant in maintaining social harmony amidst the challenges of modernization.